Structural Features of LiPON Glasses Determined by 1D and 2D 31P MAS NMR. (18th May 2015) - Mascaraque, Nerea; Durán, Alicia; Muñoz, Francisco; Tricot, Gregory
Abstract : The relationships between structure and electrical properties of nitrided lithium phosphate glasses (LiPON) used as electrolytes for lithium batteries are key issues for better understanding and design of these materials. For the first time, the effect of nitrogen introduction in the structure of lithium phosphorus oxynitride glasses, formulated over a wide range of composition 38–55 mol.% of Li2 O, has been studied through 31 P 1D/2D MAS NMR experiments. Information obtained from 2D 31 P/ 31 P correlation maps has been used to deconvolute the 1D 31 P NMR spectra and allowed establishing the percentage of oxide phosphate groups (PO4 ) and phosphorus species with nitrogen (P(O, N)4 ) as well as the connectivity scheme of the phosphate network. Finally, it has been demonstrated that the lithium content affects the structural changes induced by the introduction of nitrogen. In particular, the lower the lithium content is, the lower the total percentage of nitrided P(O, N)4 species is.